THE OPTION OF USING THE PARAMEDIAN FOREHEAD FLAP TO ELIMINATE DEFORMATIONS OF THE EXTERNAL NOSE AFTER TREATMENT OF CANCER (CLINICAL OBSERVATION) - T. V. Ostrinskaya; A. М. Zhumankulov (Опухоли головы и шеи, 2015)
The article tells about the possibilities of recovering of cicatricial deformities and extensive defects of external nose with the using of paramedian forehead flap and free rib cartilage. Despite its antiquity, this method is still relevant, providing a good cosmetic and functional results.